1994
DOI: 10.1021/bi00177a035
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of interaction of Escherichia coli threonine synthase with substrates and inhibitors

Abstract: Threonine synthase (TS), the last enzyme of the threonine biosynthetic pathway, catalyzes L-threonine formation from L-homoserine phosphate (HSerP; Km = 0.5 mM, V = 440 min-1) and DL-vinylglycine. Furthermore, TS catalyzes beta-elimination reactions with L-serine (Km = 150 mM, V = 4.7 min-1), DL-3-chloroalanine, L-threonine, and L-allo-threonine as substrates to yield pyruvate or alpha-ketobutyrate, while L-alanine, L-2-aminobutanoic acid, and L-2-amino-5-phosphonopentanoic acid are substrates for half-transam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
72
1

Year Published

1995
1995
2010
2010

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(76 citation statements)
references
References 25 publications
3
72
1
Order By: Relevance
“…The extreme survival defects of S. cerevisiae thr1⌬ and thr4⌬ mutants in vivo, the inhibition of hyphal formation, the attenuated survival of C. albicans thr1⌬ mutants, and the essentiality of these genes in C. neoformans (34) all validate the potential of Thr1p and Thr4p as antifungal drug targets. Several inhibitors, including phosphohomoserine analogs (17) and the phosphohomoserine analog-containing peptides rhizocticin and plumbemycin (38,40), have been identified that target bacterial threonine synthase; however, the therapeutic efficacy of each is limited since many peptides are subject to serum protease digestion (30,47), various phosphohomoserine analogs are also N-methyl-D-aspartate (NMDA) receptor antagonists (57), and we found no inhibition of yeast by D,L-threo-␤-hydroxyaspartic acid or D,L-2-amino-5-phosphonovaleric acid (data not shown). Nonetheless, the rapidity and profound lethality observed upon exposure of thr1⌬ and thr4⌬ mutants to serum and threonine starvation conditions indicate that Thr1p and Thr4p inhibitors would be fungicidal in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…The extreme survival defects of S. cerevisiae thr1⌬ and thr4⌬ mutants in vivo, the inhibition of hyphal formation, the attenuated survival of C. albicans thr1⌬ mutants, and the essentiality of these genes in C. neoformans (34) all validate the potential of Thr1p and Thr4p as antifungal drug targets. Several inhibitors, including phosphohomoserine analogs (17) and the phosphohomoserine analog-containing peptides rhizocticin and plumbemycin (38,40), have been identified that target bacterial threonine synthase; however, the therapeutic efficacy of each is limited since many peptides are subject to serum protease digestion (30,47), various phosphohomoserine analogs are also N-methyl-D-aspartate (NMDA) receptor antagonists (57), and we found no inhibition of yeast by D,L-threo-␤-hydroxyaspartic acid or D,L-2-amino-5-phosphonovaleric acid (data not shown). Nonetheless, the rapidity and profound lethality observed upon exposure of thr1⌬ and thr4⌬ mutants to serum and threonine starvation conditions indicate that Thr1p and Thr4p inhibitors would be fungicidal in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative determination of individual 2-oxoacids was performed as described previously (Laber et al, 1994). Plant material was frozen in liquid nitrogen and homogenized in 25 mM Mops-NaOH buffer, pH 7.1 (300 pL/g fresh weight).…”
Section: Analysis Of 2-oxoacidsmentioning
confidence: 99%
“…1B). The bacterial reaction was studied by following the absorbence of PLP and was shown to present at least seven steps (Laber et al 1994).In plants, OPH is a branch point intermediate between the methionine/S-adenosyl-methionine (SAM) and threonine/ isoleucine pathways (Giovanelli et al 1984). Thus TS competes for OPH with cystathionine-␥-synthase (CGS), the first committed enzyme in the methionine pathway (Fig.…”
mentioning
confidence: 99%